Chip conducting polymer tantalum capacitor with stable leakage current and preparation method thereof

By using a water-retaining conductive polymer cathode layer and a barrier layer in the conductive polymer tantalum capacitor, the problem of unstable leakage current in the capacitor in a high humidity environment is solved, and higher stability and reliability are achieved.

CN119724935APending Publication Date: 2025-03-28BEIJING 718 YOUYI ELECTRONICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411300031.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Conductive polymer tantalum capacitors are prone to cause equivalent series resistance failure and leakage current failure in high humidity environments, and water vapor generated by high temperature during welding may cause cracking of the shell, resulting in unstable leakage current.

Method used

Using a water-retaining conductive polymer cathode layer and a barrier layer, the internal moisture is maintained by adding a water-retaining additive to the cathode material of the tantalum capacitor, and a barrier layer is added to the outer layer to reduce moisture loss and block external moisture.

Benefits of technology

It effectively improves the leakage current stability and reliability of tantalum capacitors, enhances moisture resistance, and ensures the stable operation of the capacitor under different environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724935A_ABST
    Figure CN119724935A_ABST
Patent Text Reader

Abstract

The invention discloses a chip conducting polymer tantalum capacitor with stable leakage current and a preparation method thereof, and belongs to the field of capacitors. The method comprises the following steps: coating the surface of the dielectric layer with the pretreatment layer to enhance the adhesive force between the dielectric layer and the water-retaining conductive polymer cathode layer; the pretreatment layer is sequentially coated with a water-retaining inner layer containing a water-retaining additive, a transition layer and an outer layer to form a water-retaining conductive polymer cathode layer, and the adhesive force between sub-layers of the outer layer is improved through a cross-linking agent; the end face of the tantalum anode core leading out the tantalum wire is coated with an insulating protection layer; a graphite layer and a silver paste layer are coated, and two electrodes are led out through a lead frame; and adding a barrier layer on the surface of the tantalum capacitor core group and molding and packaging a shell to prepare the tantalum capacitor. Water vapor in the polymer tantalum capacitor prepared by the method is stabilized at a certain level and is slightly influenced along with temperature change, and the direct current leakage current level of the capacitor is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid tantalum capacitors, and in particular to a chip-type conductive polymer tantalum capacitor with stable leakage current and a preparation method thereof. Background Art

[0002] In recent years, conductive polymers have been used as cathode materials for solid tantalum capacitors due to their high conductivity and good stability. Compared with traditional manganese dioxide cathodes, conductive polymers can effectively reduce the equivalent series resistance (ESR) of tantalum capacitors and have better high-frequency performance. However, from the current point of view, capacitors with conductive polymers as cathode materials still have several problems. The reliability issues associated with conductive polymer tantalum capacitors are mainly due to the sensitivity of conductive polymers to environmental stress.

[0003] Long-term exposure of polymer tantalum capacitors to high humidity environments will cause equivalent series resistance parameter failures and may lead to leakage current failures. In addition, a large amount of water vapor caused by high temperature is generated during the welding process, which may cause the shell to crack. However, excessive drying may cause polymer tantalum capacitors to have a momentary short circuit at the initial moment after voltage is applied, which lasts much longer than normal charging. The leakage current of tantalum capacitors is extremely difficult to stabilize in a short period of time, with transient leakage currents lasting for several seconds or minutes. The presence of an appropriate amount of water can speed up the process of leakage current stabilization, and at the same time, water as a plasticizer can enhance the self-healing effect of conductive polymer tantalum capacitors. Therefore, how to maintain the stability of the internal moisture content of tantalum capacitors and thereby enhance the stability of the leakage current and the reliability of use of polymer capacitors is a problem that needs to be solved.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a chip-type conductive polymer tantalum capacitor with stable leakage current, which improves the stability and reliability of the leakage current of the tantalum capacitor by improving the water retention characteristics of the conductive polymer cathode material of the tantalum capacitor and the overall waterproof performance of the tantalum capacitor, thereby solving the above-mentioned technical problems existing in the prior art.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A chip-type conductive polymer tantalum capacitor with stable leakage current, comprising:

[0008] Tantalum anode core, dielectric layer, pretreatment layer, water-retaining conductive polymer cathode layer, insulating protective layer, graphite silver paste layer, barrier layer, positive electrode lead, negative electrode lead and packaging shell; wherein,

[0009] The surface of the tantalum anode core is covered with a dielectric layer, the outside of the dielectric layer is covered with a pretreatment layer, and the outside of the pretreatment layer is covered with a water-retaining conductive polymer cathode layer except for the end surface of the tantalum anode core where the tantalum wire is led out;

[0010] The end surface of the tantalum anode core leading out the tantalum wire is coated with an insulating protective layer;

[0011] The water-retaining conductive polymer cathode layer is covered with a graphite layer and a silver paste layer in sequence, and then a positive electrode lead and a negative electrode lead are led out through a lead frame to obtain a tantalum capacitor core group;

[0012] The surface of the tantalum capacitor core group is coated with a barrier layer and molded and packaged in a packaging shell;

[0013] The other ends of the positive electrode lead and the negative electrode lead are both led out of the packaging shell.

[0014] A method for preparing a chip-type conductive polymer tantalum capacitor with stable leakage current according to the present invention comprises:

[0015] Step 1: Form Ta on the surface after energization 2 O 5 The anode tantalum block of the dielectric layer is immersed in the pretreatment solution and then dried to form a pretreatment layer on the surface of the anode tantalum block;

[0016] Step 2, coating the outside of the pretreatment layer except the end surface of the tantalum anode core where the tantalum wire is led out with a conductive polymer cathode layer added with a water-retaining additive, to obtain a tantalum anode core coated with a water-retaining conductive polymer cathode layer;

[0017] Step 3, coating an insulating protective layer on the end surface of the tantalum wire leading out of the tantalum anode core;

[0018] Step 4, coating the water-retaining conductive polymer cathode layer with a graphite layer and a silver paste layer in sequence, and then leading out a positive electrode lead and a negative electrode lead through a lead frame to obtain a tantalum capacitor core assembly;

[0019] Step 5, coating a barrier layer on the surface of the tantalum capacitor core group and molding a packaging shell, so that the other ends of the positive electrode lead and the negative electrode lead extend out of the packaging shell, thus manufacturing a chip-type conductive polymer tantalum capacitor with stable leakage current.

[0020] Compared with the prior art, the chip-type conductive polymer tantalum capacitor with stable leakage current provided by the present invention has the following beneficial effects:

[0021] By using a water-retaining conductive polymer cathode layer, the tantalum capacitor can maintain a stable amount of moisture inside. At the same time, adding a barrier layer to the outer layer of the tantalum capacitor core group can reduce the loss of internal moisture on the one hand, and prevent external moisture from entering the capacitor on the other hand, improving the product's moisture resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0023] Figure 1 A schematic cross-sectional structure diagram of a conductive polymer tantalum capacitor provided in an embodiment of the present invention.

[0024] Figure 2 A flow chart of a method for preparing a conductive polymer tantalum capacitor provided in an embodiment of the present invention.

[0025] In the figure: 1-anode tantalum block; 2-tantalum wire; 3-dielectric layer; 4-pretreatment layer; 5-water-retaining conductive polymer cathode layer; 6-insulating protective layer; 7-graphite layer; 8-silver paste layer; 9-packaging shell; 10-positive electrode lead; 11-negative electrode lead; 12-silver paste; 13-soldering point. DETAILED DESCRIPTION

[0026] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in combination with the specific content of the present invention; it is obvious that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, which does not constitute a limitation of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.

[0027] First, the terms that may be used in this article are explained as follows:

[0028] The term “and / or” means that either or both of them can be realized at the same time. For example, X and / or Y means both “X” or “Y” and “X and Y”.

[0029] The terms "include", "comprises", "contains", "has" or other descriptions with similar semantics should be interpreted as non-exclusive inclusion. For example, including certain technical feature elements (such as raw materials, components, ingredients, carriers, dosage forms, materials, dimensions, parts, components, mechanisms, devices, steps, procedures, methods, reaction conditions, processing conditions, parameters, algorithms, signals, data, products or products, etc.) should be interpreted as including not only certain technical feature elements explicitly listed, but also other technical feature elements known in the art that are not explicitly listed.

[0030] The term "consisting of..." means excluding any technical feature elements not explicitly listed. If this term is used in a claim, it will make the claim closed, so that it does not contain technical feature elements other than the technical feature elements explicitly listed, except for the conventional impurities related to them. If this term only appears in a clause of a claim, it only limits the elements explicitly listed in the clause, and the elements recorded in other clauses are not excluded from the overall claim.

[0031] Unless otherwise specified or limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example: it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this article can be understood according to specific circumstances.

[0032] When concentration, temperature, pressure, size or other parameters are expressed in the form of a numerical range, the numerical range should be understood to specifically disclose all ranges formed by the pairing of any upper limit, lower limit, and preferred value in the numerical range, regardless of whether the range is explicitly stated; for example, if a numerical range of "2 to 8" is stated, the numerical range should be interpreted as including ranges such as "2 to 7", "2 to 6", "5 to 7", "3 to 4 and 6 to 7", "3 to 5 and 7", "2 and 5 to 7", etc. Unless otherwise specified, the numerical ranges stated herein include both their end values ​​and all integers and fractions within the numerical range.

[0033] The orientation or position relationship indicated by terms such as "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", etc. are based on the orientation or position relationship shown in the drawings and are only for the convenience and simplification of description, and do not explicitly or implicitly indicate that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation of this document.

[0034] The scheme provided by the present invention is described in detail below. The contents not described in detail in the embodiments of the present invention belong to the prior art known to professionals in the field. If the specific conditions are not specified in the embodiments of the present invention, they are carried out according to the conventional conditions in the field or the conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used in the embodiments of the present invention, they are all conventional products that can be purchased commercially.

[0035] like Figure 1As shown, an embodiment of the present invention provides a chip-type conductive polymer tantalum capacitor with stable leakage current, comprising:

[0036] Tantalum anode core, dielectric layer, pretreatment layer, water-retaining conductive polymer cathode layer, insulating protective layer, graphite silver paste layer, barrier layer, positive electrode lead, negative electrode lead and packaging shell; wherein,

[0037] The surface of the tantalum anode core is covered with a dielectric layer, the outside of the dielectric layer is covered with a pretreatment layer, and the outside of the pretreatment layer is covered with a water-retaining conductive polymer cathode layer except for the end surface of the tantalum anode core where the tantalum wire is led out;

[0038] The end surface of the tantalum anode core leading out the tantalum wire is coated with an insulating protective layer;

[0039] The water-retaining conductive polymer cathode layer is covered with a graphite layer and a silver paste layer in sequence, and then a positive electrode lead and a negative electrode lead are led out through a lead frame to obtain a tantalum capacitor core group;

[0040] The surface of the tantalum capacitor core group is coated with a barrier layer and molded and packaged in a packaging shell;

[0041] The other ends of the positive electrode lead and the negative electrode lead are both led out of the packaging shell.

[0042] Preferably, in the above-mentioned tantalum capacitor, the water-retaining conductive polymer cathode layer consists of a water-retaining inner layer, a transition layer and an outer layer;

[0043] The pretreatment layer is a coating formed of a monomer containing a hydroxyl functional group, a polymer containing a hydroxyl functional group, an organofunctional silane or a hydrolyzate thereof, a natural organic compound or a polymer;

[0044] The barrier layer is formed by curing a hydrophobic material and an auxiliary agent, and the thickness of the barrier layer is 0.2 μm to 200 μm.

[0045] Preferably, in the above-mentioned tantalum capacitor, the water-retaining conductive polymer cathode layer is deposited by nano-poly 3,4-ethylenedioxythiophene particle dispersion, wherein the particle sizes of the poly 3,4-ethylenedioxythiophene particles used in the water-retaining inner layer, transition layer and outer layer are 10-50nm, 20-80nm and 50-100nm respectively;

[0046] The water-retaining inner layer contains a water-retaining additive.

[0047] Preferably, in the above-mentioned tantalum capacitor, the water-retaining additive is an organic compound or an inorganic compound with a hydrophilic functional group, and the hydrophilic functional group includes at least one or more of a hydroxyl group, a carboxyl group, an amino group, a carbonyl group, a sulfonic acid group, and a thiol group;

[0048] The organic material used in the barrier layer is at least one of a silane material, an acrylic material, a polyurethane material, and an epoxy resin material; the inorganic material is Al 2 O 3 , ceramics or at least one thereof.

[0049] Preferably, in the above-mentioned tantalum capacitor, the hydrophilic functional group is one or more of polyvinyl alcohol, polyethylene glycol, hydrophilic polyimide, hydrophilic polyurethane, polyacrylic acid, carboxymethyl cellulose, starch, acrylic acid, methyl acrylate, and chitosan.

[0050] Preferably, in the above tantalum capacitor, a crosslinking agent layer is provided between adjacent polymer sublayers of the outer layer of the water-retaining conductive polymer cathode layer.

[0051] Preferably, in the above tantalum capacitor, the crosslinking agent layer is made of polycationic salts, amine compounds or their derivatives.

[0052] Preferably, in the above-mentioned tantalum capacitor, the polymer containing hydroxyl functional groups used in the pretreatment layer is a polymer containing hydroxyl repeating units and a copolymer thereof;

[0053] The organofunctional silane is one or more of aminosilane, vinylsilane and epoxysilane;

[0054] The natural organic compound is one or more of olive oil, oleic acid, linoleic acid and soybean oil.

[0055] The pretreatment layer is coated between the dielectric layer and the water-retaining conductive polymer cathode layer, and can enhance the adhesion between the dielectric layer and the water-retaining conductive polymer cathode layer.

[0056] like Figure 2 As shown, the embodiment of the present invention also provides a method for preparing the above-mentioned chip-type conductive polymer tantalum capacitor with stable leakage current, comprising:

[0057] Step 1: Form Ta on the surface after energization 2 O 5 The anode tantalum block of the dielectric layer is immersed in the pretreatment solution and then dried to form a pretreatment layer on the surface of the anode tantalum block;

[0058] Step 2, coating the outside of the pretreatment layer except the end surface of the tantalum anode core where the tantalum wire is led out with a conductive polymer cathode layer added with a water-retaining additive, to obtain a tantalum anode core coated with a water-retaining conductive polymer cathode layer;

[0059] Step 3, coating an insulating protective layer on the end surface of the tantalum wire leading out of the tantalum anode core;

[0060] Step 4, coating the water-retaining conductive polymer cathode layer with a graphite layer and a silver paste layer in sequence, and then leading out a positive electrode lead and a negative electrode lead through a lead frame to obtain a tantalum capacitor core assembly;

[0061] Step 5, coating a barrier layer on the surface of the tantalum capacitor core group and molding a packaging shell, so that the other ends of the positive electrode lead and the negative electrode lead extend out of the packaging shell, thus manufacturing a chip-type conductive polymer tantalum capacitor with stable leakage current.

[0062] Preferably, in step 1 of the above method, the pretreatment liquid is a solution formed by any one of a monomer containing a hydroxyl functional group, a polymer containing at least two hydroxyl repeating units and a copolymer thereof, an organofunctional silane, a natural organic compound or a polymer and a solvent;

[0063] In step 1, the surface after energization is formed into Ta in the following manner: 2 O 5 The anode tantalum block of the dielectric layer is immersed in the pretreatment solution to form a pretreatment layer on the surface of the anode tantalum block, including:

[0064] The surface is formed into Ta 2 O 5 The anode tantalum block of the dielectric layer is immersed in a pretreatment solution at a temperature of 20 to 60° C. for 2 to 10 minutes at a speed of 0.03 mm to 0.5 mm / s, then placed at room temperature for 5 to 15 minutes, and dried at 50 to 200° C. for 30 minutes to form a pretreatment layer;

[0065] In the step 2, the conductive polymer dispersion used in the conductive polymer cathode layer to which a water-retaining additive is added comprises: polyanion composite particles, wherein the polyanion is a PSS copolymer;

[0066] The added water-retaining additive is: an organic compound or an inorganic compound with a hydrophilic functional group, wherein the hydrophilic functional group includes: one or more of a hydroxyl group, a carboxyl group, an amino group, a carbonyl group, a sulfonic acid group, and a thiol group;

[0067] In the step 2, the dielectric layer of the anode tantalum block is coated with a conductive polymer cathode layer added with a water-retaining additive in the following manner to obtain a tantalum anode core coated with a water-retaining conductive polymer cathode layer, comprising:

[0068] Step 21, immersing the anode tantalum block with a pretreatment layer formed on the surface of the dielectric layer in a conductive polymer dispersion with a solid content of 0.5% to 2.5% and a water-retaining additive of 5% to 50% by mass at a speed of 0.05 to 0.5 mm / s for 1 to 10 minutes, and then drying at 100° C. to 150° C. for 20 minutes, and repeating this step 3 to 10 times to form a water-retaining inner layer;

[0069] Step 22, immersing the anode tantalum block treated in step 21 in a conductive polymer dispersion with a solid content of 1% to 5% at a speed of 0.05 to 0.5 mm / s for 1 to 10 minutes, and then drying it at 75° C. to 150° C. for 20 minutes, and repeating this step 2 to 8 times to form a transition layer;

[0070] Step 23, immersing the anode tantalum block treated in step 22 in a conductive polymer dispersion with a solid content of 2% to 10% at a speed of 0.05 to 0.5 mm / s for 1 to 10 minutes, and then drying it at 75°C to 150°C for 30 minutes, immersing the dried anode tantalum block in a cross-linking agent for 1 to 5 minutes, and then drying it at 120°C to 150°C for 20 minutes, repeating this step alternately 2 to 6 times to form an outer layer, and finally forming a water-retaining conductive polymer cathode layer that does not cover the front end surface of the anode tantalum block.

[0071] The water-retaining conductive polymer cathode layer is formed by a water-retaining inner layer, a transition layer and an outer layer, and the adhesion between the sub-layers of the outer layer is improved by a cross-linking agent.

[0072] Preferably, in step 3 of the above method, an insulating protective layer is coated on the end face of the tantalum wire leading out of the tantalum anode core in the following manner: a polymer resin is used as a raw material, and the coating completely covers the end face of the tantalum wire leading out of the tantalum anode core. After coating, the coating is allowed to stand at room temperature for 10 to 30 minutes, and then transferred to an oven at 125°C to 200°C for complete curing, thereby obtaining an insulating protective layer.

[0073] Preferably, in step 5 of the above method, the barrier layer coated on the surface of the tantalum capacitor core group is a continuous and dense thin film layer obtained by curing a polymer resin or a continuous and dense thin film layer obtained by physical deposition or chemical deposition of an inorganic material;

[0074] The barrier layer has a thickness of 0.2 μm to 200 μm.

[0075] In summary, the tantalum capacitor implemented by the present invention uses a water-retaining conductive polymer cathode layer with a water-retaining additive to stably maintain an appropriate amount of moisture inside the tantalum capacitor. At the same time, a barrier layer is added to the outer layer of the tantalum capacitor core group, which can reduce the loss of internal moisture on the one hand, and prevent external moisture from entering the capacitor, thereby improving the moisture resistance of the product.

[0076] In order to more clearly demonstrate the technical solution and technical effects provided by the present invention, the solution provided by the embodiment of the present invention is described in detail with specific embodiments below.

[0077] Example 1

[0078] like Figure 1As shown, this embodiment provides a chip-type conductive polymer tantalum capacitor with stable leakage current, and its structure includes:

[0079] Tantalum anode core 1, dielectric layer 3, pretreatment layer 4, water-retaining conductive polymer cathode layer 5, insulating protective layer 6, graphite layer 7, silver paste layer 8, barrier layer 9, positive electrode lead 11, negative electrode lead 12 and packaging shell 10; wherein,

[0080] The surface of the tantalum anode core is provided with a dielectric layer, the outside of the dielectric layer is covered with a pretreatment layer, the outside of the pretreatment layer is covered with a water-retaining conductive polymer cathode layer except for the end surface of the tantalum anode core from which the tantalum wire is led out, and the end surface of the tantalum anode core from which the tantalum wire is led out is coated with an insulating protective layer;

[0081] The water-retaining conductive polymer cathode layer is covered with a graphite layer and a silver paste layer in sequence, and then a positive electrode lead and a negative electrode lead are led out through a lead frame to obtain a tantalum capacitor core group;

[0082] The surface of the tantalum capacitor core group is coated with a barrier layer and then molded and packaged to form a packaging shell;

[0083] The other ends of the positive electrode lead and the negative electrode lead are both led out of the packaging shell.

[0084] Furthermore, the pretreatment layer in the above tantalum capacitor is made of any one of a monomer containing a hydroxyl functional group, a polymer containing a hydroxyl functional group, an organic functional silane, a hydrolyzate of an organic functional silane, a natural organic compound, and a natural organic polymer.

[0085] In the above-mentioned pretreatment layer, the polymers containing hydroxyl functional groups used include: polymers containing hydroxyl repeating units such as polyethylene glycol and polyvinyl alcohol and their copolymers; the organic functionalized silane is one or more of aminosilane, vinyl silane, epoxy silane, etc.; the natural organic compound is one or more of olive oil, oleic acid, linoleic acid, and soybean oil.

[0086] Furthermore, in the above tantalum capacitor, a water-retaining additive is added to the water-retaining conductive polymer cathode layer to keep a certain amount of water inside the tantalum capacitor. Specifically, the water-retaining conductive polymer cathode layer is composed of a water-retaining inner layer, a transition layer and an outer layer, and the water-retaining additive is added to the water-retaining inner layer.

[0087] Preferably, the water-retaining additive is an organic compound or an inorganic compound with a hydrophilic functional group, wherein the hydrophilic functional group includes one or more of a hydroxyl group, a carboxyl group, an amino group, a carbonyl group, a sulfonic acid group, and a thiol group. The hydrophilic functional group may be polyvinyl alcohol, polyethylene glycol, a hydrophilic polyimide, a hydrophilic polyurethane, polyacrylic acid, carboxymethyl cellulose, starch, acrylic acid, methyl acrylate, chitosan, and the like.

[0088] Specifically, the water-retaining conductive polymer cathode layer is formed by deposition of nano-poly 3,4-ethylenedioxythiophene particle dispersion. The particle sizes of the poly 3,4-ethylenedioxythiophene particles used in the water-retaining inner layer, transition layer and outer layer are 10-50nm, 20-80nm and 50-100nm respectively. The water-retaining inner layer is used for capacity extraction, the transition layer is used to connect the water-retaining inner layer and the outer layer to improve product stability, and the outer layer is a protective layer.

[0089] Furthermore, the outer layer of the water-retaining conductive polymer cathode layer has multiple polymer sublayers. A crosslinking agent layer is provided between adjacent polymer sublayers to improve edge and corner adhesion and interlayer bonding strength. Preferably, the crosslinking agent layer can be a polycationic salt, an amine compound or a derivative thereof.

[0090] Each sublayer of the water-retaining conductive polymer cathode layer is deposited and formed in the form of dipping and drying.

[0091] Furthermore, a barrier layer is coated on the surface of the tantalum capacitor core group to isolate water vapor, inhibit the volatilization of internal water vapor, and prevent external water vapor from entering. Preferably, the barrier layer is solidified by a hydrophobic material and an additive. The organic material used for the hydrophobic material is usually silane, acrylic, polyurethane, epoxy resin and other materials; the inorganic material used is usually Al 2 O 3 , ceramics, etc. The thickness of the barrier layer is usually 0.2 μm to 200 μm, wherein, if a polymer film is used as the barrier layer, the typical thickness of the barrier layer is 10 μm to 200 μm, and in some embodiments, it is 15 μm to 85 μm, and if an inorganic material film is used as the barrier layer, the typical thickness of the barrier layer is 0.2 μm to 50 μm, and in some embodiments, it is 0.2 μm to 10 μm.

[0092] The above-mentioned packaging shell adopts molded packaging.

[0093] Example 2

[0094] like Figure 2 As shown, this embodiment provides a method for preparing a chip-type conductive polymer tantalum capacitor with a stable leakage current, which is to realize a stable cathode structure through a multi-stage forming process for an energized anode tantalum block, and the specific method steps are as follows:

[0095] Step 1) Forming Ta on the surface after energization 2 O 5 The anode tantalum block of the dielectric layer is immersed in the pretreatment solution for 2 to 10 minutes, the temperature of the treatment solution is 25°C to 60°C, and is dried and formed at 50°C to 200°C to form a pretreatment layer on the surface of the dielectric layer of the anode tantalum block;

[0096] Step 2) The anode tantalum block with the pretreatment layer formed on the surface of the dielectric layer in step 1 is immersed in a dispersion of poly (3,4-ethylenedioxythiophene) particles added with a water-retaining additive in a proportion of 5% to 50% under vacuum for 1 to 10 minutes, and dried under a vacuum environment of 75° C. to 150° C., and this step is repeated 3 to 25 times to form a water-retaining conductive polymer cathode layer on the other three surfaces of the anode tantalum block except the end surface of the tantalum wire, to obtain a tantalum anode core coated with the water-retaining conductive polymer cathode layer;

[0097] Step 3) coating an insulating protective layer on the end face of the tantalum anode core where the tantalum wire is led out, then sequentially impregnating graphite outside the water-retaining conductive polymer cathode layer to form a graphite layer, impregnating silver paste outside the graphite layer to form a silver paste layer, and then using a lead frame to lead out a positive electrode lead and a negative electrode lead, the negative electrode lead is welded through the silver paste 14, and the positive electrode lead is welded through the welding point 13, to obtain a tantalum capacitor core assembly;

[0098] Step 4) coating a barrier layer on the outside of the prepared tantalum capacitor core group, and then performing molding and packaging to form a packaging shell, thereby obtaining a chip-type conductive polymer tantalum capacitor with a stable leakage current.

[0099] In the above step 1, the pretreatment liquid can be any one of a polyhydroxyl functional polymer, an organofunctional silane, a natural organic compound or a polymer; the polyhydroxyl functional polymer includes: a polymer containing at least two repeating units of hydroxyl groups such as polyethylene glycol and polyvinyl alcohol and a copolymer thereof;

[0100] The organofunctional silane includes one or more of aminosilane, vinylsilane, epoxysilane, etc.;

[0101] The natural organic compound or polymer includes any one of olive oil, oleic acid, linoleic acid and soybean oil.

[0102] The solvent in the pretreatment solution is one or more of water, alcohols, ethers, and ketones, such as methanol, ethanol, propanol, isopropanol, methyl ether, ethyl ether, methyl tert-butyl ether, anisole, acetone, butanone, and the like.

[0103] Specifically, the surface is formed into Ta 2 O 5The anode tantalum block of the dielectric layer is immersed in a pretreatment solution at a temperature of 20 to 60°C at a speed of 0.03 mm to 0.5 mm / s for 2 to 10 minutes, then placed at room temperature for 5 to 15 minutes, and dried at 50 to 200°C for 30 minutes; in one embodiment, the pretreatment solution is polyvinyl alcohol or polyethylene glycol and its copolymer, with a mass content of about 0.01% to 1%, and in some embodiments, the mass content is about 0.05% to 5%. In one embodiment, the treatment solution is an organic functional silane, with a mass content of about 0.005% to 2%, and in some embodiments, the mass content is about 0.1% to 3%.

[0104] In the above step 2, the conductive polymer cathode layer can be divided into a water-retaining inner layer, a transition layer, and an outer layer according to the different solid content of the impregnated polymer dispersion, each layer includes a plurality of polymer sublayers, and all are obtained after the polymer dispersion is dried and solidified. A crosslinking agent layer is provided between adjacent conductive polymer sublayers of the outer layer to improve interlayer adhesion and corner adhesion rate. The crosslinking agent layer includes a polycationic salt, compound or amine compound.

[0105] The water-retaining additive is any one of an organic compound containing a hydrophilic functional group, an organic polymer containing a hydrophilic functional group, an inorganic compound containing a hydrophilic functional group, and an inorganic polymer containing a hydrophilic functional group. The hydrophilic functional group may be one or more of a hydroxyl group, a carboxyl group, an amino group, a carbonyl group, a sulfonic acid group, and a thiol group. It may be polyvinyl alcohol, polyethylene glycol, a hydrophilic polyimide, a hydrophilic polyurethane, polyacrylic acid, carboxymethyl cellulose, starch, acrylic acid, methyl acrylate, chitosan, and the like. The water-retaining additive is added only when the inner polymer layer is prepared.

[0106] The water-retaining conductive polymer cathode layer formed in the step does not cover the end surface of the tantalum anode core where the tantalum wire is led out.

[0107] Specifically, in step 2, a water-retaining conductive polymer cathode layer is formed on the other three surfaces of the anode tantalum block except the end surface of the tantalum wire lead-out in the following manner, including:

[0108] Step 21, immersing the anode tantalum block with a pre-treated layer formed on the surface in a dispersion of poly (3,4-ethylenedioxythiophene) particles with a solid content of about 0.5% to 2.5% and added with 5% to 50% of a water-retaining additive at a speed of 0.05 to 0.5 mm / s under vacuum for 1 to 10 minutes, and drying at 100° C. to 150° C. for 20 minutes, repeating this step 3 to 10 times to obtain a water-retaining inner layer, and then conducting capacity extraction;

[0109] Step 22, immersing the above-mentioned anode tantalum block in a dispersion of poly (3,4-ethylenedioxythiophene) particles with a solid content of about 1% to 5% at a speed of 0.05 to 0.5 mm / s under vacuum for 1 to 10 minutes, and drying it at 75° C. to 150° C. for 20 minutes, repeating this step 2 to 8 times to obtain a transition layer to enhance the stability of the cathode layer;

[0110] Step 23, immerse the above-mentioned anode tantalum block in a dispersion of poly (3,4-ethylenedioxythiophene) particles with a solid content of about 2% to 10% at a speed of 0.05 to 0.5 mm / s under vacuum for 1 to 10 minutes, and dry it at 75°C to 150°C for 30 minutes. Then immerse the dried core in a cross-linking agent for 1 to 5 minutes, and dry it at 120°C to 150°C for 20 minutes. Repeat this step 2 to 6 times to obtain an outer layer, and finally form a continuous and dense polymer film layer of suitable thickness, which is a water-retaining conductive polymer cathode layer.

[0111] In the above step 3, the insulating protective layer is a material with certain flexibility and hydrophobicity. It can be a film layer formed by materials such as silicone resin, epoxy resin, phenolic resin, polyester, polyurethane, polyimide, insulating paint, etc. Specifically, the insulating protective layer is cured by polymer resin, and the polymer resin can be epoxy resin, polyurethane, polyimide, insulating paint and other materials. When the insulating protective layer is applied, it is necessary to completely cover the end face of the tantalum anode core where the tantalum wire is led out. After coating, it is left to air at room temperature for 10 to 30 minutes, and then transferred to a 125°C to 200°C oven for complete curing.

[0112] In the above step 5, the barrier layer is formed by curing a material with a certain flexibility and hydrophobicity and an auxiliary agent. The flexible and hydrophobic material can be a silane, epoxy, polyurethane or other material. Specifically, the barrier layer is a continuous and dense film material, which can be obtained by curing a polymer resin, or by physical or chemical deposition. The polymer resin can be acrylic, polyimide, polyurethane, epoxy resin, silane, fluorine-containing polymer or other materials. Other dense metal oxide films or inorganic non-metal films can be Al 2 O 3 , ceramics and other inorganic materials. The thickness of the barrier layer is usually 0.2μm to 200μm, of which the typical thickness in the case of polymer films is 10μm to 200μm, and in some implementation cases is 15μm to 85μm, and the typical thickness of inorganic material films is 0.2μm to 50μm, and in some implementation cases is 0.2μm to 10μm.

[0113] This embodiment adds a certain proportion of water-retaining material to the polymer cathode material of the tantalum capacitor to keep a proper amount of water inside the capacitor. At the same time, a barrier layer is added to the outer layer of the core group, which can reduce the loss of internal water and prevent external water from entering the capacitor, thereby improving the moisture resistance of the product.

[0114] Example 3

[0115] See also Figure 1 This embodiment provides a chip-type conductive polymer tantalum capacitor with stable leakage current, which is a 35V47μF E-shell chip-type conductive polymer tantalum electrolytic capacitor product, and its preparation method includes:

[0116] First, tantalum powder with a specific capacity of 18000μF·V / g was mixed evenly with 2% (mass ratio) of binder, and after the powder was dried, it was pressed into an anode sample with a sample size of 4.8×3.3×3.3 and a weight of 314mg, and sintered at 1550℃. Then it was immersed in a phosphoric acid solution with a conductivity of 4.2mS / cm and oxidized to 110V; then the anodized tantalum anode block was immersed in a polyimide pretreatment solution with a temperature of 35℃ and a content of 0.1% at a speed of 0.3mm / s for 10min, left at room temperature for 5min, and dried at 180℃ for 10min;

[0117] The tantalum anode block coated with the pretreatment layer is immersed in a dispersion of poly(3,4-ethylenedioxythiophene) particles with a solid content of about 1.5% and added with 10% wt polyacrylic acid at a speed of 0.3 mm / s for 10 minutes under vacuum, and dried at 120° C. for 20 minutes. This step is repeated 6 times; then immersed in a dispersion of poly(3,4-ethylenedioxythiophene) particles with a solid content of about 2% at a speed of 0.3 mm / s for 5 minutes under vacuum, and dried at 120° C. for 20 minutes. This step is repeated 5 times; finally, immersed in a dispersion of poly(3,4-ethylenedioxythiophene) particles with a solid content of about 3% at a speed of 0.15 mm / s for 5 minutes under vacuum, and dried at 120° C. for 30 minutes, then the dried core is immersed in a crosslinking agent for 5 minutes, and dried at 120° C. for 20 minutes. This step is repeated 4 times alternately to form a water-retaining conductive polymer cathode layer;

[0118] After the preparation of the water-retaining conductive polymer cathode layer, a 50% epoxy resin is coated on the upper end surface, and then left to air at room temperature for 10 minutes, and then transferred to a 160°C oven for curing for 30 minutes. The product is then impregnated with graphite silver paste, and the electrodes are led out through a lead frame to obtain a tantalum capacitor core assembly;

[0119] The tantalum capacitor core group is immersed in a 30% by mass silicone resin treatment liquid to treat the core group surface, and the excess part is cleaned with a solvent, and then the core group is placed at 180°C for 1 hour for curing. After curing, it is naturally cooled at room temperature to form a protective film as a barrier layer on the surface of the core group; finally, the tantalum capacitor core group is molded and packaged according to the normal process to assemble into a tantalum capacitor numbered ①. Take 5 qualified products and record their DC leakage current values.

[0120] Comparative Example 1

[0121] Except that the water-retaining additive (polyacrylic acid) is not used, a tantalum capacitor numbered ② is produced according to the method of Example 3. Five qualified products are selected and their DC leakage current values ​​are recorded.

[0122] Comparative Example 2

[0123] Except that the water-retaining additive (polyacrylic acid) and the silicone resin barrier layer are not used, a capacitor numbered ③ is produced according to the method of Example 3. Five qualified products are selected and their DC leakage current values ​​are recorded.

[0124] It can be known that the above Comparative Examples 1 and 2 are both designed to evaluate the effects of the water-retaining conductive polymer cathode layer and the barrier layer, and do not completely belong to the prior art.

[0125] The comparison of the leakage current changes of the three groups of tantalum capacitors prepared above at room temperature and after high temperature drying is shown in Table 1 below:

[0126] Table 1 Sample DC leakage current test results

[0127]

[0128] By comparing the DC leakage current data in Table 1 above, it can be seen that the leakage current of the five capacitors numbered ① is the most stable. This shows that the tantalum capacitor product of the present invention, due to the provision of a water-retaining conductive polymer cathode layer and a barrier layer, not only retains internal moisture but also blocks external water vapor, thereby ensuring the stability of the leakage current. Moreover, after drying at 125°C for 168 hours, a smaller leakage current is ensured, thereby improving the stability and reliability of the leakage current of the tantalum capacitor.

[0129] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims. The information disclosed in the background technology section of this article is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as an admission or in any form that the information constitutes prior art known to those skilled in the art.

Claims

1. A chip-type conductive polymer tantalum capacitor with stable leakage current, characterized in that: include; Tantalum anode core, dielectric layer, pretreatment layer, water-retaining conductive polymer cathode layer, insulating protective layer, graphite silver paste layer, barrier layer, positive electrode lead, negative electrode lead and packaging shell; wherein, The surface of the tantalum anode core is covered with a dielectric layer, the outside of the dielectric layer is covered with a pretreatment layer, and the outside of the pretreatment layer is covered with a water-retaining conductive polymer cathode layer except for the end surface of the tantalum anode core where the tantalum wire is led out; The end surface of the tantalum anode core leading out the tantalum wire is coated with an insulating protective layer; The water-retaining conductive polymer cathode layer is covered with a graphite layer and a silver paste layer in sequence, and then a positive electrode lead and a negative electrode lead are led out through a lead frame to obtain a tantalum capacitor core group; The surface of the tantalum capacitor core group is coated with a barrier layer and molded and packaged in a packaging shell; The other ends of the positive electrode lead and the negative electrode lead are both led out of the packaging shell.

2. The chip-type conductive polymer tantalum capacitor with stable leakage current according to claim 1, characterized in that: The water-retaining conductive polymer cathode layer is composed of a water-retaining inner layer, a transition layer and an outer layer; The pretreatment layer is a coating formed of a monomer containing a hydroxyl functional group, a polymer containing a hydroxyl functional group, an organofunctional silane or a hydrolyzate thereof, a natural organic compound or a polymer; The barrier layer is formed by curing a hydrophobic material and an auxiliary agent, and the thickness of the barrier layer is 0.2 μm to 200 μm.

3. The chip-type conductive polymer tantalum capacitor with stable leakage current according to claim 2, characterized in that: The water-retaining conductive polymer cathode layer is deposited by nanometer poly 3,4-ethylenedioxythiophene particle dispersion, wherein the particle sizes of the poly 3,4-ethylenedioxythiophene particles used in the water-retaining inner layer, transition layer and outer layer are 10-50nm, 20-80nm and 50-100nm respectively; The water-retaining inner layer contains a water-retaining additive.

4. The chip-type conductive polymer tantalum capacitor with stable leakage current according to claim 3, characterized in that: The water-retaining additive is an organic compound or an inorganic compound with a hydrophilic functional group, and the hydrophilic functional group includes at least one or more of a hydroxyl group, a carboxyl group, an amino group, a carbonyl group, a sulfonic acid group, and a thiol group; Among the hydrophobic materials used in the barrier layer, the organic material is at least one of silane materials, acrylic materials, polyurethane materials, and epoxy resin materials; the inorganic material is at least one of Al2O3 and ceramics.

5. The chip-type conductive polymer tantalum capacitor with stable leakage current according to claim 4, characterized in that: The hydrophilic functional group is one or more of polyvinyl alcohol, polyethylene glycol, hydrophilic polyimide, hydrophilic polyurethane, polyacrylic acid, carboxymethyl cellulose, starch, acrylic acid, methyl acrylate, and chitosan.

6. The chip-type conductive polymer tantalum capacitor with stable leakage current according to claim 3, characterized in that: The outer layer of the water-retaining conductive polymer cathode layer has a crosslinking agent layer between adjacent polymer sublayers.

7. The chip-type conductive polymer tantalum capacitor with stable leakage current according to claim 6, characterized in that: The crosslinking agent layer is made of polycationic salts, amine compounds or derivatives thereof.

8. The chip-type conductive polymer tantalum capacitor with stable leakage current according to claim 3, characterized in that: In the pretreatment layer, the polymer containing hydroxyl functional groups used is a polymer containing hydroxyl repeating units and a copolymer thereof; The organofunctional silane is one or more of aminosilane, vinylsilane and epoxysilane; The natural organic compound is one or more of olive oil, oleic acid, linoleic acid and soybean oil.

9. A method for preparing a chip-type conductive polymer tantalum capacitor with stable leakage current according to any one of claims 1 to 8, characterized in that: include: Step 1, immersing the anode tantalum block with a Ta2O5 dielectric layer formed on the surface after energization into a pretreatment solution, and then drying and forming, so as to form a pretreatment layer on the surface of the anode tantalum block; Step 2, coating the outside of the pretreatment layer except the end surface of the tantalum anode core where the tantalum wire is led out with a conductive polymer cathode layer added with a water-retaining additive, to obtain a tantalum anode core coated with a water-retaining conductive polymer cathode layer; Step 3, coating an insulating protective layer on the end surface of the tantalum wire leading out of the tantalum anode core; Step 4, coating the water-retaining conductive polymer cathode layer with a graphite layer and a silver paste layer in sequence, and then leading out a positive electrode lead and a negative electrode lead through a lead frame to obtain a tantalum capacitor core assembly; Step 5, coating a barrier layer on the surface of the tantalum capacitor core group and molding a packaging shell, so that the other ends of the positive electrode lead and the negative electrode lead extend out of the packaging shell, thus manufacturing a chip-type conductive polymer tantalum capacitor with stable leakage current.

10. The method for preparing a chip-type conductive polymer tantalum capacitor with stable leakage current according to claim 9, characterized in that: In step 1, the pretreatment liquid is a solution formed by any one of a monomer containing a hydroxyl functional group, a polymer containing at least two hydroxyl repeating units and a copolymer thereof, an organic functional silane, a natural organic compound or a polymer and a solvent; In the step 1, the anode tantalum block having a Ta2O5 dielectric layer formed on the surface after energization is immersed in a pretreatment solution to form a pretreatment layer on the surface of the anode tantalum block in the following manner, including: The anode tantalum block with a Ta2O5 dielectric layer formed on the surface is immersed in a pretreatment solution with a temperature of 20 to 60° C. at a speed of 0.03 mm to 0.5 mm / s for 2 to 10 minutes, then placed at room temperature for 5 to 15 minutes, and dried at 50 to 200° C. for 30 minutes to form a pretreatment layer; In the step 2, the conductive polymer dispersion used in the conductive polymer cathode layer to which a water-retaining additive is added comprises: polyanion composite particles, wherein the polyanion is a PSS copolymer; The added water-retaining additive is: an organic compound or an inorganic compound with a hydrophilic functional group, wherein the hydrophilic functional group includes: one or more of a hydroxyl group, a carboxyl group, an amino group, a carbonyl group, a sulfonic acid group, and a thiol group; In the step 2, the outside of the pretreatment layer except the end surface of the tantalum anode core from which the tantalum wire is led is coated with a conductive polymer cathode layer added with a water-retaining additive in the following manner to obtain a tantalum anode core coated with a water-retaining conductive polymer cathode layer, comprising: Step 21, immersing the anode tantalum block with a pre-treated layer formed on the surface in a conductive polymer dispersion with a solid content of 0.5% to 2.5% and a water-retaining additive of 5% to 50% by mass at a speed of 0.05 to 0.5 mm / s for 1 to 10 minutes, and then drying at 100° C. to 150° C. for 20 minutes, and repeating this step 3 to 10 times to form a water-retaining inner layer; Step 22, immersing the anode tantalum block treated in step 21 in a conductive polymer dispersion with a solid content of 1% to 5% at a speed of 0.05 to 0.5 mm / s under vacuum for 1 to 10 minutes, and then drying it at 75° C. to 150° C. for 20 minutes, and repeating this step 2 to 8 times to form a transition layer; Step 23, immersing the anode tantalum block treated in step 22 in a conductive polymer dispersion with a solid content of 2% to 10% at a speed of 0.05 to 0.5 mm / s under vacuum for 1 to 10 minutes, then drying at 75° C. to 150° C. for 30 minutes, immersing the dried anode tantalum block in a cross-linking agent for 1 to 5 minutes, then drying at 120° C. to 150° C. for 20 minutes, repeating this step alternately 2 to 6 times to form an outer layer, and finally forming a water-retaining conductive polymer cathode layer that does not cover the front end surface of the anode tantalum block; In the step 3, an insulating protective layer is coated on the end surface of the tantalum wire leading out of the tantalum anode core in the following manner: a polymer resin is used as a raw material, and the coating completely covers the end surface of the tantalum wire leading out of the tantalum anode core, and after coating, it is left to air at room temperature for 10 to 30 minutes, and then transferred to a 125° C. to 200° C. oven for complete curing, so as to obtain an insulating protective layer; In the step 5, the barrier layer coated on the surface of the tantalum capacitor core group is a continuous and dense thin film layer obtained by curing a polymer resin or a continuous and dense thin film layer obtained by physical deposition or chemical deposition of an inorganic material; The barrier layer has a thickness of 0.2 μm to 200 μm.

Citation Information

Cited By

  • Moisture-proof laminated solid aluminum electrolytic capacitor and preparation method thereof

    CN120854169A